Cyberbullying entre adolescentes beneficiarios del área DEMUNA de la Municipalidad Distrital San José-Pacasmayo en el año 2021 - Chilón Julca, Claudia Lizbeth (2021)
Analyze cyberbullying in the teaching-learning process of adolescent beneficiaries of the DEMUNA of the San José-Pacasmayo District Municipality in the year 2021. This research is of an applied type, since knowledge about a specific social reality will be applied. The type is quantitative, since it refers to data that can be quantified, and we study different cases through surveys, building characteristics that are explained with general realities. 1. It was determined that the conditions that generate cyberbullying are related to the interaction of virtual platforms, institutional invisibility and the separation of parents in the teaching-learning process of the adolescent beneficiaries of the DEMUNA of the San José District Municipality- Pacasmayo in the year 2021.